Impact of the COVID-19 pandemic on community-dwelling older adults: A longitudinal qualitative study of participants from the Hertfordshire Cohort Study. - Ilse Bloom; Jean Zhang; Julia Hammond; Gregorio Bevilacqua; Wendy Lawrence; Kate A Ward; Cyrus Cooper; Elaine M Dennison (PLoS ONE)
Background Older adults have been especially vulnerable to adverse effects from the COVID-19 pandemic including higher mortality and more severe disease complications. At the same time, social isolation, malnutrition and physical inactivity are serious concerns among older adults. The pandemic and associated restrictions may serve to exacerbate these issues, presenting increased risks to physical and mental health. The aims of this qualitative study were: i) to explore how community-living older people in the UK experienced the first wave of the COVID-19 pandemic, specifically how it impacted their well-being and associated health behaviours; ii) to explore how older people's experiences and behaviours changed over time throughout the first wave. Methods Qualitative data were collected by conducting serial telephone interviews, with an interval of approximately three months. Participants were from the Hertfordshire Cohort Study, all aged over 80 years. Discussions were audio-recorded, information related to the COVID-19 pandemic was transcribed verbatim and transcripts analysed thematically. Interviews were conducted from March to October 2020. Results Data for twelve participants (7 men and 5 women) from a total of 35 interviews were used, comprising two or three timepoints per participant. Analysis identified five overarching themes: 1) shopping strategies and food accessibility, 2) limitations on activities and going out, 3) disruption to healthcare, 4) social and psychological repercussions, and 5) coping strategies. Findings highlight challenges associated with accessing shops, healthcare, and usual activities due to pandemic-related restrictions. Longitudinal findings showed that for some, the ongoing pandemic and related restrictions appeared to aggravate mental health issues (low mood, anxiety) over time, as well as greater feelings of isolation or loneliness, reduced activity and functional limitations; this was despite some relaxation of restrictions later on. Coping strategies used by participants included finding ways to keep busy and to do physical activity safely, maintaining social contact remotely, and having an optimistic or positive outlook, a 'do what you can' attitude. Conclusions Interventions are likely to be needed in the wake of the COVID-19 pandemic to support health behaviours, such as increasing physical activity, social engagement and improving mental health among community-living older adults.